Overexpressed β‐cyanoalanine synthase functions with alternative oxidase to improve tobacco resistance to salt stress by alleviating oxidative damage. Issue 8 (2nd January 2020) - Yu, Lu‐Lu; Liu, Yang; Liu, Cui‐Jiao; Zhu, Feng; He, Zheng‐Quan; Xu, Fei
Abstract : β‐Cyanoalanine synthase (β‐CAS) is an enzyme involved in cyanide detoxification. However, little information is available regarding the effects of β‐CAS activity changes on plant resistance to environmental stress. Here, we found that β‐CAS overexpression (CAS‐OE) improves the resistance of tobacco plants to salt stress, whereas plants with β‐CAS silencing suffer more oxidative damage than wild‐type plants. Notably, blocking respiration by the alternative oxidase (AOX) pathway significantly aggravates stress injury and impairs the salt stress tolerance mediated by CAS‐OE. These findings present novel insights into the synergistic effect between β‐CAS and AOX in protecting plants from salt stress, where β‐CAS plays a vital role in restraining cyanide accumulation, and AOX helps to alleviate the toxic effect of cyanide. Abstract :